2007
DOI: 10.1007/s11270-007-9567-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Silica Retention and Its Impact on Eutrophication in a Complex of Mountain Reservoirs

Abstract: This paper reports on studies conducted during 2005 in the ecosystem of the SolinaMyczkowce mountain complex of mesotrophic reservoirs on the San River, SE Poland. Of the 1,950 t of dissolved silica calculated to flow into the reservoirs in the course of the year, c. 20% of the load was retained in the reservoirs. However, most of this retention took place in the lower Myczkowce Reservoir. Far-reaching depletion to below 10 μM L −1 of silicate was noted during the summer in the epilimnetic waters of the two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
1
21
0
2
Order By: Relevance
“…3.5 kT Si year − 1 . Presently, it has been accepted that the "artificial lake effect" caused by the dam construction, should be responsible for the silicon retention, which has been observed in impounded rivers worldwide, such as Danube , Changjiang (Li et al, 2007;Wang et al, 2007), Seine (Jossette et al, 1999), San River (Koszelnik and Tomaszek 2007), Columbia River in Canada (Matzinger et al, 2007), as well as some smaller rivers (Humborg et al, 2002) . However, reservoirs in this study showed the reverse effects on DSi, that is, only WJD is the sink for Si, and other three are sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3.5 kT Si year − 1 . Presently, it has been accepted that the "artificial lake effect" caused by the dam construction, should be responsible for the silicon retention, which has been observed in impounded rivers worldwide, such as Danube , Changjiang (Li et al, 2007;Wang et al, 2007), Seine (Jossette et al, 1999), San River (Koszelnik and Tomaszek 2007), Columbia River in Canada (Matzinger et al, 2007), as well as some smaller rivers (Humborg et al, 2002) . However, reservoirs in this study showed the reverse effects on DSi, that is, only WJD is the sink for Si, and other three are sources.…”
Section: Discussionmentioning
confidence: 99%
“…As a macronutrients required by certain groups of plants, e.g. diatom, DSi plays an important role in sustaining river, coastal and oceanic ecosystems (Jossette et al, 1999;Neal et al 2005;Koszelnik and Tomaszek 2007). Diatoms, contributing 25% of the world's entire net primary production (Willén, 1991), are the most important group of planktonic algae in marine ecosystem .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koszelnik and Tomaszek (2008) discussed the role of the N:P:Si ratio not only in marine environments but also in freshwater ecosystems such as natural lakes. The regular monitoring of the DSi or N:P:Si ratio is thus important, especially in lakes and estuaries subjected to intense human activities.…”
Section: Introductionmentioning
confidence: 99%